Health Professionals' Perceptions and Practice of Family Centred Care for Children Injured in Road Traffic Accidents: A Qualitative Study in Ghana - Ohene, L.A.; Power, K.J.; Raghu, R. (Journal of Pediatric Nursing, 2020)
The Family Centered Care (FCC) model iswidely recognized as the standard for pediatric care practice in the context of families and hospitalized children. Healthcare professionals' knowledge of the FCCmodel is therefore central to its successful implementation. Nonetheless, there is paucity of scholarship in the Ghanaian context, regarding professionals' knowledge and practice of FCC. Objectives: This study, being the first in the Ghanaian context aimed to explore the perceptions of family centered care among healthcare professionals who provide the healthcare needs of children hospitalized through road traffic accidents. Method: Twenty-four (24) healthcare professionals were interviewed as part of a larger study which adopted a Grounded Theory approach. Data collection and analysis occurred concurrently. Here, we employed constant comparative methods to structure emerging categories and sub-categories. Findings: Most health professionals in the study perceived family centered care to mean family involvement, although obvious inconsistencies characterized existing practices. Based on contextual perspectives, three categories emerged, namely; parental involvement, communication and setting boundaries. Conclusion: The concept of FCC is a familiar terminology among health professionals. However, its principles, components and dimensions in the western context are alien to healthcare professionals in Ghana. A contextspecific FCC model which reflects social values and cultural norms is therefore required for healthcare services to children and families in Ghana
Research Article
Keywords: Ghana; Family centered care; Family involvement; Professionals; Road traffic accidents